Melon seed drying kinetics described by a diffusion model (Research, Society and Development, 2020)
The present work aimed to perform the drying kinetics of melon seeds at different drying temperatures and to adjust the diffusion model to the experimental data considering the geometry of an infinite cylinder. The drying was carried out in an air circulation oven at temperatures of 50, 60 and 70 ºC and with an air speed of 1.5 m s-1, based on the data obtained and considering the melon seeds with infinite cylinder geometry. The parameters were calculated by the analytical solution using the diffusion equation. The coefficient of determination showed values above 0.99 and low values of the chi-square function, indicating that the diffusion model presented satisfactory adjustment to the experimental data of the drying kinetics of melon seeds. According to the data obtained in the drying kinetics of melon seeds, it was seen that the effective diffusivity, the heat transfer coefficient and the Biot number showed a strong positive correlation, indicating that the temperature increase was directly proportional to the values of the parameters calculated diffusion rates. The increase in temperature favors mass transfer, decreasing the dynamic equilibrium humidity and drying time, which varied from 1020, 940 and 880 minutes to temperatures of 50, 60 and 70 °C, it appears that for the longest interval greater time variations were the humidity variations inside the seed.